Simbol v Jenkovi liriki - Matajc, Vanesa (Primerjalna književnost, 2001)
Simon Jenko and the structure of symbolic content. - In comparison to the classic-romantic poetry of France Prešeren (1800-1849), the post-romantic poetry of Simon Jenko (1835-1869) introduces a structure of symbolic content into shorter, formally less demanding texts, all of them in the poem/image form. They appear either as part of a wider cycle (Obrazi - Faces) or on their own. Expressively. a poem/image corresponds to the post-romantic lyrical subject, and they both increase the scope of text symbolisation.
Keywords: Jenko, Simon, 1835-1869; Slovene literature; slovenska književnost; slovenska poezija; literarne študije; simbolika